The European orientation among the writers of "Lanka"-MARSU in the context of the literary debate of 1925-1928. (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article under consideration deals with the European orientation of the writers, who were the members of the literary group “LANKA-MARS”. Such orientation is expressed by means of their literary heritage, publicist materials, and the position in literary discussion of 1925−1928. B. Antonenko-Davydovych, G. Kosynka, V. Pidmohylnyy, E. Pluzhnyk and the other members of literary group tried to be in the context of the temporary tendencies in the world literature development, neglecting mass and provinciality in literature.
Keywords: literary discussion; literary group; European orientation